PENDEKATAN KOMUNIKASI ORANG TUA KEPADA ANAK DALAM MEMBERIKAN PEMAHAMAN TERHADAP TAYANGAN TELEVISI - putri kinanti bahar (Jurnal Ilmu Komunikasi UHO : Jurnal Penelitian Kajian Ilmu Komunikasi dan Informasi, 2016)
ABSTRACT The problem in this research is how to shape the approach of parents in giving an understanding of television on children of primary school age. The location of this research was conducted in the Old Market District of Mandonga Complex Kendari. The determination of these locations based on the consideration that the average parent in the Old Market Complexes have children of primary school age who are also fond of watching television and requires the application of appropriate forms of communication in order to provide an understanding of television on children. This study uses a qualitative method with an informant as much as eleven people. The results showed that the kind of approach the parents in giving an understanding of impressions Television at primary school age children in the complex of the Old Market District of Mandonga Kendari consists of the stages of communication between persona that gives understanding and expressing the views of children with communication directly to children to express the views can provide a good understanding of the positive and the negative of such impressions that can deepen ties of affection between parents and children. Keywords: communications approach parents to children on television